1997
DOI: 10.1007/s002130050438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hot tea, coffee and water ingestion on physiological responses and mood: the role of caffeine, water and beverage type

Abstract: Psychopharmacological studies using caffeinated beverages or caffeine have rarely considered temporal effects on psychological and physiological function or the specific contribution of caffeine, hot water, or beverage type to the observed effects. The effect of 400 ml hot tea, coffee, and water consumption on systolic and diastolic blood pressure (SBP and DBP), heart rate, skin conductance (a measure of sympathetic nervous system activation), skin temperature, salivary cortisol, and mood were monitored in 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
8
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 33 publications
6
95
8
1
Order By: Relevance
“…Peeling & Dawson, 2007). Placebo-controlled trials using objective measures can corroborate these reports; consumption of caffeine can produce significant improvements in: reaction time, short-term memory, vigilance, reasoning, response accuracy, attention, and general alertness (see Glade, 2010) Paralleling its effects on cognition, caffeine consumption is also accompanied by improved mood including increased 'happiness' (Amendola, Gabrieli & Lieberman, 1998), a reduction in depressive symptoms (Childs & de Wit, 2008), and decreased anxiety (Quinlan, Lane & Aspinall, 1997), although there are conflicting results with respect to anxiety (Broderick & Benjamin, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Peeling & Dawson, 2007). Placebo-controlled trials using objective measures can corroborate these reports; consumption of caffeine can produce significant improvements in: reaction time, short-term memory, vigilance, reasoning, response accuracy, attention, and general alertness (see Glade, 2010) Paralleling its effects on cognition, caffeine consumption is also accompanied by improved mood including increased 'happiness' (Amendola, Gabrieli & Lieberman, 1998), a reduction in depressive symptoms (Childs & de Wit, 2008), and decreased anxiety (Quinlan, Lane & Aspinall, 1997), although there are conflicting results with respect to anxiety (Broderick & Benjamin, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Taken orally, caffeine reaches a peak plasma level between 30 and 75 minutes after ingestion (53). The half-life of caffeine has been reported to be 4 to 5 hours with a modest intake of coffee, but longer when the dose exceeds 300 mg; this value may vary between acute and chronic users (41,42,61).…”
Section: Caffeine Timingmentioning
confidence: 99%
“…Caffeine may result in dizziness, headache, jitteriness, nervousness, insomnia, and gastrointestinal distress, generally at doses greater than 9 and 13 mgÁkg 21 of caffeine for nonusers and users, respectively (12,19,41,53). These signs and symptoms at high doses may be linked to decreased performance in some athletes (24,28,54).…”
mentioning
confidence: 99%
“…Some people, for instance, find that taking a pain medicine or using a cold or hot pack works faster and better when they relax at the same time. Quinian et al [21] based on psychopharmacological studies concluded that ingestion of hot caffeinated beverages stimulates physiological processes faster than hitherto described, primarily via the effects of hot water and caffeine, but with beverage type and milk playing important modulatory roles.…”
Section: Physical Effectmentioning
confidence: 99%
“…The improvement of mood is among the effects attributed to caffeine in coffee drinkers [21]. Over consumption of coffee increase caffeine content of body which suppresses the serotonin, it leads to depression.…”
Section: Coffeementioning
confidence: 99%